Fungal and bacterial Mycetoma diagnosis from a histological perspective: a local report of two cases involving foreign labourers - Yahaya, Balqis; Lai, Shau Kong; Mohd Ali, Razana; Hussin, Huzlinda (Universiti Putra Malaysia, 2021)
Mycetoma is a chronic subcutaneous granulomatous inflammation due to infection by fungus (Eumycetes) and bacteria (Actinomycetes) by penetrating inoculation of the microorganism into an injured skin. Late presentation is common, which leads to various deformities. In a standard setting, mycetoma diagnosis requires a combination of clinical assessment, histopathological features, and culture. However, microbiological culture takes time to be ready. Therefore, the classical histomorphological features supported by histochemical stains are the options to provide a fast diagnosis for the commencement of appropriate treatment. We described two cases of eumycetoma and actinomycetoma, emphasising the differences in their histomorphological features and histochemical stains that may facilitate the diagnosis.